Trinity: nexus of the mysteries of Christian faith - Hunt, Anne (Theology in global perspective, 2005)
The development of trinitarian theology in the patristic and medieval periods -- Contemporary approaches to trinitarian theology -- Trinity and christology -- Trinity, the paschal mystery, and soteriology -- Trinity and creation, ecology and evolution -- Trinity and church -- Trinity and the world religions -- Trinity, grace, and the moral life -- Trinity, spirituality, and worship -- Trinity and eschatology -- Conclusion: the mysteries of Christian faith in a trinitarian setting